2004
DOI: 10.1108/00483480410510606
|View full text |Cite
|
Sign up to set email alerts
|

Employee development:an organizational justice perspective

Abstract: The present study examined possible links between elements of perceived procedural justice, global fairness perception and attitudinal measures in a review/ development context. Organizational justice and possible correlates were reviewed resulting in four hypotheses. Data was collected from 132 employees of the UK arm of an international new media agency via a web-based survey. It was found that a psychometric instrument based on Gilliland's (1993) ten rules of procedural justice proved a valuable framework i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 46 publications
1
57
0
5
Order By: Relevance
“…16,[18][19][20][21] One concept that connects how employees are treated with motivation and job satisfaction is that of organisational justice, 22 which generally encompasses three components: distributive justice, procedural justice and interactional justice. 23 Distributive justice refers to how fairly employees feel they are treated (in comparison to others) with regards to the distribution of resources and outcomes. 23,24 Does the person think they are getting the workload, work schedule, salary level, promotion and allowances they deserve?…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…16,[18][19][20][21] One concept that connects how employees are treated with motivation and job satisfaction is that of organisational justice, 22 which generally encompasses three components: distributive justice, procedural justice and interactional justice. 23 Distributive justice refers to how fairly employees feel they are treated (in comparison to others) with regards to the distribution of resources and outcomes. 23,24 Does the person think they are getting the workload, work schedule, salary level, promotion and allowances they deserve?…”
mentioning
confidence: 99%
“…23 Distributive justice refers to how fairly employees feel they are treated (in comparison to others) with regards to the distribution of resources and outcomes. 23,24 Does the person think they are getting the workload, work schedule, salary level, promotion and allowances they deserve? Do they perceive that outcomes are fair, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The perceptions of fairness of the system are an important aspect that contributes to its effectiveness [20]. Understanding the employee's attitude and behaviour about the PAS in organizations is important as they are key to determine the effectiveness [21]. Zakaria et al (2012) [22] reported that (HRM practices can develop the performance of an organisation by con-tributing to employee satisfaction.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Understanding the employee's attitude and behaviour about the PAS in organizations is important as they are key to determine the effectiveness [21]. Zakaria et al (2012) [22] reported that (HRM practices can develop the performance of an organisation by con-tributing to employee satisfaction. The performance appraisal is arguably one of the more critical factor in terms of organisation performance and appears to be an indispensable part of any HRM system when compared among the HR practices studied [23].…”
Section: Review Of Literaturementioning
confidence: 99%